ExpTimer: timer software to facilitate complex, multi-step procedures. (17th April 2013) - Luyten, Laura; Van Cappellen, Frederik
ExpTimer is free, user-friendly timer software that can come in handy when you are running timed, multi-step protocols, e.g. behavioral experiments, histological stainings or any other (scientific) procedure consisting of a set of consecutive actions. It was written in Visual C# and can be found at http://sourceforge.net/projects/exptimer. You can easily upload your own protocol and ExpTimer will guide you through the different steps of your procedure. The program shows the progress and current stage of your protocol, what the next step will be and notifies you with a sound signal of when to take it. As such, ExpTimer facilitates your experiments by simplifying the execution of complex, multi-step procedures and by improving accuracy and replicability, particularly when time is an important factor.